2015
DOI: 10.1111/hex.12344
|View full text |Cite
|
Sign up to set email alerts
|

Combined verbal and numerical expressions increase perceived risk of medicine side‐effects: a randomized controlled trial of EMA recommendations

Abstract: Background The study evaluated European Medicines Agency (EMA) recommendations on communicating frequency information on side-effect risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…Current guidelines suggest PILs should combine the verbal risk descriptors with the numerical expressions [16]; however, we argue this is not enough, as it still leads to overestimation [17, 18]. If combined expressions are used, it remains important to use the correct verbal risk descriptor that is interpreted by people in the same way as the numerical expression that is associated with it.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines suggest PILs should combine the verbal risk descriptors with the numerical expressions [16]; however, we argue this is not enough, as it still leads to overestimation [17, 18]. If combined expressions are used, it remains important to use the correct verbal risk descriptor that is interpreted by people in the same way as the numerical expression that is associated with it.…”
Section: Discussionmentioning
confidence: 99%
“…The PILs for the sample of recently licensed medicines was more likely to use the EMA recommended format than PILs for the most frequently dispensed medicines, suggesting that PILs may need to be updated more frequently. Use of the risk format has occurred despite a lack of empirical backing for it and indeed suggestions that it may lead to misjudgements of risk in some patients [7]. There remains a need for further research to test alternative formats for risk communication in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…[2]. However it is notable that the effects of the EU recommended risk expressions have not been evaluated formally [7]. The use of verbal terms alone (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Patients tend to overestimate the likelihood of adverse effects when non-numeric, qualitative descriptors (e.g., common, rare) are used to communicate risk likelihood instead of, or in addition to, numerical information (e.g., 10% of patients; 1 in 10 patients) alone. 18,19 Overestimates of risk likelihood can make patients less willing to take a medication. 16,20 In a previous study by this research team that was guided by fuzzy trace theory (FTT), [21][22][23] it was demonstrated that simply informing individuals that a specific adverse effect may occur M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%